Guided wave propagation in a multilayered magneto-electro-elastic curved panel by Chebyshev spectral elements method. (1st January 2019) - Xiao, Dongliang; Han, Qiang; Jiang, Tengjiao
Abstract: This paper investigates the dispersion characteristics of guided waves in a multilayered magneto-electro-elastic curved panel. Based on the Hamilton principle, the Chebyshev spectral element method is applied along the radial and circumferential directions to obtain the dispersion equation of the waves. The advantage of the spectral element method over a high degree piecewise polynomial basis function is the high order of accuracy. The influences on the dispersion characteristics is analyzed in terms of four factors: structural radian, magneto-electro effect, thickness-diameter ratio, and stacking sequence. In addition, the dispersion curves in the curved panel display a phenomenon which different from plate and hollow cylinders: mode conversion. We explain this from the perspective of physics and mathematics, separately. The structural radian and thickness-diameter ratio show the most significant effect on the mode conversion.